Assessing the potential and limitations of leveraging food sovereignty to improve human health - Andrew D Jones; Lilly Fink Shapiro; Mark L. Wilson (Frontiers Media S.A., 2015)
Food sovereignty has been defined as the right of peoples to healthy and culturally appropriate food produced through ecologically sound and sustainable methods, and their right to define their own food and agriculture systems. Human health is an implied component of this definition through the principle of healthy food. In fact, improved human health is commonly cited as a benefit of transforming food production away from the dominant practices of industrial agriculture. Yet, does the use of ecologically sound and sustainable methods of food production necessarily translate into better human health outcomes? Does greater choice in defining an agricultural or food system create gains in health and well-being? We elucidate the conceptual linkages between food sovereignty and human health, critically examine the empirical evidence supporting or refuting these linkages, and identify research gaps and key priorities for the food sovereignty-human health research agenda. Five domains of food sovereignty are proposed including 1) use of agroecological management practices for food production, 2) the localizing of food production and consumption, 3) promotion of social justice and equity, 4) valuation of traditional knowledge, and 5) transforming economic and political institutions and structures to support self-determination. We find that although there are many plausible linkages between food sovereignty and human health, the empirical evidence in support of the hypothesis that increasing food sovereignty yields improvements to human health is weak. We propose that a concerted effort to generate new empirical evidence on the health implications of these domains of food sovereignty is urgently needed, and discuss areas of research that may be crucial for addressing the gaps in the evidence base.